Recombinant sugarcane cystatin CaneCPI-5 promotes osteogenic differentiation - Fernandes, Célio Junior da Costa [UNESP]; Cassiano, Ana Flávia Balestrero [UNESP]; Henrique-Silva, Flavio; Cirelli, Joni Augusto [UNESP]; de Souza, Eduardo Pereira; Coaguila-Llerena, Hernán [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Faria, Gisele [UNESP] (Elsevier, 2023)
Cysteine proteases orchestrate bone remodeling, and are inhibited by cystatins. In reinforcing our hypothesis that exogenous and naturally obtained inhibitors of cysteine proteases (cystatins) act on bone remodeling, we decided to challenge osteoblasts with sugarcane-derived cystatin (CaneCPI-5) for up to 7 days. To this end, we investigated molecular issues related to the decisive, preliminary stages of osteoblast biology, such as adhesion, migration, proliferation, and differentiation. Our data showed that CaneCPI-5 negatively modulates both cofilin phosphorylation at Ser03, and the increase in cytoskeleton remodeling during the adhesion mechanism, possibly as a prerequisite to controlling cell proliferation and migration. This is mainly because CaneCPI-5 also caused the overexpression of the CDK2 gene, and greater migration of osteoblasts. Extracellular matrix remodeling was also evaluated in this study by investigating matrix metalloproteinase (MMP) activities. Our data showed that CaneCPI-5 overstimulates both MMP-2 and MMP-9 activities, and suggested that this cellular event could be related to osteoblast differentiation. Additionally, differentiation mechanisms were better evaluated by investigating Osterix and alkaline phosphatase (ALP) genes, and bone morphogenetic protein (BMP) signaling members. Altogether, our data showed that CaneCPI-5 can trigger biological mechanisms related to osteoblast differentiation, and broaden the perspectives for better exploring biotechnological approaches for bone disorders.
Keywords: Bone; Cathepsin; Cell differentiation; Osteoblasts; Phytocystatin